Merancang dan Mensimulasi Infinite Impulse Response Chebyshev Low-Pass Digital Filter Menggunakan Perangkat FPGA - Wijayanti, Mariza (Jurnal Ilmiah Teknologi dan Rekayasa, 2014)
This study will present filter design. The first step is determining the filter specification, next, calculating the low pass, high pass, and band-pass of IIR filter, then simulating the design calculation result using MATLAB, and last, implementing the design using FPGA. Direct form is considered to be the approach in realizing digital filter. IIR filter is implemented in Spartan-IIIxc3s500c-4fg320 FPGA and simulated by assisted with Xilinx ISE 9.2i. The software is used in code synthesis and simulation. The code of IIR filter fixed focus form has been realized. The modules used are multiplier, adder, and delay. The result of data simulation then is compared with Matlab program output. Based on the result of filter comparisons, the error occurs because of the component of Divider use which rounding the result of dividing process.Keywords: Filter, IIR, FPGA, Xilinx-Ise 9.2i, Matlab